Before perceptual narrowing: The emergence of the native sounds of language. (27th May 2022) - Zacharaki, Konstantina; Sebastian‐Galles, Nuria
Abstract: The present study investigates the precursors of representations of phonemes in 4.5‐month‐olds. The emergence of phonemes has been mainly studied within the framework of perceptual narrowing, that is, infants tuning to their native language and losing sensitivity to non‐native speech. One of the mechanisms behind this phenomenon is distributional learning. In this article, we tested the preference of 4.5‐month‐old infants using lists of pseudowords that resemble the vowel distribution of the native or a non‐native language. We found that infants prefer listening to the lists mirroring the native language. The results suggest that infants can extract vowel information from novel stimuli, and they can map it on pre‐existing knowledge on vowels that leads to a preference for the native lists.